Munājāt and Ibn al-ʿArabī's Unity of Being - Lear, Amanda (Religions, 2023)
This paper looks at the mystical topic of munājāt, or intimate dialogue, typically between a worshipper and their Lord, and how it relates to Ibn al-‘Arabī’s waḥdat al-wujūd (Unity of Being). The paper first works to situate munājāt within the current surrounding body of Sufi devotional literature and within the Islamic intellectual tradition. Then the paper goes on to examine how munājāt as prayer reflects and relates to Ibn al-‘Arabī’s larger metaphysical treatises, particularly waḥdat al-wujūd, using crucial concepts such as Barzakh, Imagination, and dhikr (remembrance). From this it may be understood that munājāt is direct communication occurring from God to Himself through the form of man.